Anxiety masquerading as autonomic dysreflexia. (3rd September 2019) - Solinsky, Ryan; Linsenmeyer, Todd A.
Abstract : Context: Autonomic dysreflexia (AD) is characterized by a sudden onset of hypertension in those with spinal cord injuries (SCI) at T6 or above. Prompt recognition and treatment of AD is important. Herein are two individuals with SCI and acute hypertension due to anxiety that may easily have been confused for AD. Findings: Case 1: A 77-year-old male with C4 AIS D SCI and a history of anxiety and AD presented for urodynamics to evaluate the effectiveness of onabotulinumtoxinA injections into his urethral sphincter. After lying down on the urodynamics table, his systolic blood pressure (SBP) was noted to rise, from 138 to 170 mmHg over six minutes without any instrumentation or position change. Upon announcing urodynamics would be postponed and preparing for AD management, his SBP returned to below baseline within two minutes. Case 2: A 57-year-old male with T12 AIS A SCI and a history of anxiety presented for routine urodynamics. His baseline SBP was 140 mmHg. During bladder filling, incidental SBP was elevated to 170 mmHg. Filling was stopped and he was told the study was complete. One minute later, prior to draining his bladder, SBP decreased to 150 mmHg. Conclusions: An individual's psychological state should be considered in addition to traditional management of AD when an individual with SCI presents with hypertension. Moreover, Case 2 may possibly explain reports of individuals presenting with AD with injuries below T6.